Facile Justicia adhatoda leaf extract derived route to silver nanoparticle: synthesis, characterization and its application in photocatalytic and anticancer activity. (4th January 2019) - Latha, D; Prabu, P; Gnanamoorthy, G; Sampurnam, S; Manikandan, R; Arulvasu, C; Narayanan, V
Abstract: The aim of the present study is to investigate the photocatalytic and anticancer activity of green synthesized silver nanoparticle (AgNPs) using leaf extract of Justicia adhatoda. Several techniques were used to confirm and characterize the synthesized AgNPs. The synthesis of nanoparticle was identified by the formation of dark brown color in the reaction mixture and SPR band noted at 425 nm. The obtained AgNPs were spherical in shape with its average sizes in the ranges of 12.0, 26.7 and 47.9 nm, respectively, it can be tuned by varying the concentration of AgNO3 analyzed by High resolution Scanning Electron Microscope and Transmission Electron Microscope (HRSEM with EDAX and TEM). The formation and size distribution of obtained AgNPs were determined by Dynamic Light Scattering (DLS) method. The negative zeta potential values were observed, causing dispersion stability of synthesized AgNPs. Fourier transform infrared spectroscopy (FTIR) and Surface Enhanced Raman (SERS) analyzed the existence of alcohols, amides and etc, in the leaf extract which behave as capping and reducing agents for the synthesis. The Face Centered Cubic (FCC) nature of AgNPs was depicted by x-ray Diffraction analysis. The photocatalytic activity is established by size-dependent nature of AgNPs, using an organic dye (methylene blue) as a substrate. Besides, the AgNPs showed significant anticancer activity against Human lung cancer cell line (A549). From in-vitro investigation and dye degradation experimental studies confirmed that the synthesized AgNPs have potent photocatalytic as well as anticancer activity.